Research and reasoning of rational parameters of plumbing machinery - Прасолов, Є. Я.; Бєловол, С. А.; Черненко, Б. С.; Ужищенко, А. В. (Scientific Progress & Innovations, 2018)
The article presents the results of the study in accordance with the methodology of normative documents. The technological parameters of the plumbing machinery for growing vegetable crops are determined. At the beginning of the strip, the plumbing machinery is outputted to its original position and clinging to the traction of the tractor. The front of the plumbing roller is equipped with a tooth compactor, which is connected to the rolling pin, and the width of the frame is set: a roll with a plumbing roll and conveyor rollers and a universal knife that rotates around the axis with a clip position for cutting the plumbing with the flow control sensor of the plumbing. It includes a device for determining the direction and velocity of the compiler; sensor for determining the depth and width of the strip-dip under pinion wheels; a plant recognition sensor and a computer for processing data and making corrections to the work of the compiler, creates the optimum pressure on the paddle wheels adjusting the loader. The edges of the plumbing from the roll are fascinated by universal clamps and they are sent to the rolling wheels. The direction of motion and the speed of the compiler are controlled by the device and the data is transmitted to the computer to adjust the corrections. During the compiler's motion, the front roller makes the leveling strips at the width in front of the rolling wheels. Wheels moving during loading of the compiler under the certain optimum values ​​of the loader press the edges of the plumbing from the roll to the surface of the soil, and the rear trap clogs the film. Releases the clips of the film and return to the original position, and the plumbing at the expense of the natural tension passes through the guide rollers and unfolds along the surface of the soil. At the end of the strip, the plumbing is automatically trimmed, the plumbing machinery is raised by the lift, the tractor turns and goes to the starting position of the new strip and the process continues. Matrix planning was used to reduce the complexity and duration of the research. The dependencies of optimization parameters on influential factors are established: the diameter and angle of the soil surface of the disk with the qualified speed; diameter and depth of submersion of the soil-covering wheel and speed of movement in height. The influence of the surface of the soil on the dynamics of moisture evaporation, depending on the time of observation, is determined. The influence of the width of the plumbing on the thermal regime of the soil is established. The results of the research were tested in the PP agricultural firm «Anastasia» and LLC AF «named after Dovzhenko» VF AF «Ordanivka». The use of the plumbing is seasonal and will pay off in one year.